Aplikasi Teori Kenyaman Kolcaba dalam Asuhan Keperawatan Nyeri dan Kenyamanan pada Anak dengan Kondisi Nyeri - Wardatus Sholihah; Dessie Wanda; Happy Hayati; Erlinda Kusuma Wardani; Nurbetti Br Ginting (Journal of Telenursing (JOTING), 2026)
This study aims to determine pain and discomfort in children using Kolcaba's theory. This study used a case study design on three patients. Based on the results of the assessment of three children with pain during intravenous catheter insertion, results showed a decrease in pain scores in children after nursing interventions using Kolcaba's comfort theory to meet the pain and comfort needs of children hospitalized in the infection ward. In conclusion, nursing care using Kolcaba's comfort theory effectively reduced pain and discomfort in children in the infection ward. Keywords: Children, Pain During Intravenous Catheter Insertion, Kolcaba's Theory